Контрольна нормотворчість Президента України як важливий механізм захисту і охорони Конституції України - Берназюк, Я.; Bernaziuk, I. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
Автором здійснено дослідження контрольних нормотворчих повноважень Президента України, використання яких зумовлено необхідністю виконання главою держави функції гарантування та охорони Конституції України. Застосування цих контрольних нормотворчих повноважень також покликано забезпечити дотримання всіма суб’єктами владних повноважень, в тому числі під час видання актів нормотворчості, принципу верховенства права, що є однією з основних засад належного функціонування системи законодавства та відповідно дотримання прав і свобод людини і громадянина. The author carried out a study of features of control of law-making powers of the President of Ukraine, the use of which is caused by the need to fulfill the function of guaranteeing the head of state and the protection of the Constitution of Ukraine. Application control law-making authority should also ensure that all the subjects of power, including the time of publication of acts of law-making, rule of law principle, which is one of the grounds for the proper functioning of the system of legislation and, accordingly, the rights and freedoms of man and citizen. Issued in the course of the use of control of law-making powers of the act is an act of law-making. This is confirmed by the fact that after the abolition of certain rules of law restored the action of another, and therefore the preparation of such an act requires a complex of analytical and draft-law work. At present, it is advisable to give the division law-making to «positive» and «negative» and the transition to the approach, according to which the acts of lawmaking stands out as a subspecies of the act of control law-making.
Law-making Control of the President of Ukraine as an Important Mechanism of Protection of the Constitution of Ukraine.
Keywords: Президент України; нормотворчість; контрольна діяльність; охорона Конституції України; акт нормотворчості; President of Ukraine; norm-setting; monitoring activities; the protection of the Constitution; act of law-making